PENGARUH TERAPI MINDFULNESS TERHADAP TINGKAT STRES REMAJA DI PANTI ASUHAN AL-HASAN WATUGALUH DIWEK JOMBANG - Romadhoni, Rahayu Woro; Widiatie, Wiwiek (Jurnal EDUNursing, 2020)
Abstract Â Stress experienced by teenagers in orphanages can cause psychological disorders as well as physical disorders, if not handled appropriately. Mindfulness therapy is one of the non-pharmacological methods that can reduce stress levels, one's efforts to achieve a state of calm and can think positively in response to problems with a marked decrease in sympathetic nerve activity through positive thoughts. The aim of the study was to see the effect of mindfulness therapy on stress levels of adolescents in orphanages. One group pre and posttest design pre experimental method with a total sample of 17 respondents through total sampling technique. The independent variable is mindfulness therapy and the dependent variable is stress level. The stress level is measured by the HARS (Hamilton Anxiety Rating Scale) instrument and mindfulness therapy using the Standard Operating Procedure. Mindfulness therapy is carried out 5 times face to face for 2 weeks. Data was analyzed using the Wilcoxon test with a value of Î± = 0.05. The result is a significant difference between stress levels before and after the intervention p = 0.001 (> 0.05) which means there is influence. Mindfulness therapy balances the sympathetic nerves and parasympathetic nerves with calm so that the brain will instruct the body and mind to be calmer so that the brain can also think positively which can reduce stress levels and maintain psychological and physical health for stressed teenagers in orphanages. This research can be used as an alternative nursing action in reducing stress.Â Keywords: Mindfulness therapy, stress level, orphanage adolescent